The Study of Sustainable Agriculture Management in Gondangmanis Village, Karanganyar Regency - Almaika, Chairul; Abidin, Ali Zainal (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This research discusses sustainable agriculture in Gondangmanis Village, Karanganyar Regency. It identifies the causes of the declining number of workers and the reduction in land area within the agricultural sector. The government and the community will implement strategies to ensure the sustainability of farmers and agriculture in Gondangmanis Village. Methodology: The methodology used in this research is qualitative, with primary and secondary data sources. The study involved 10 respondents selected using porposive sampling technique from the population, with data collection through in-depth interviews with farmers, village officials, and the community. This research uses the source triangulation validity method by comparing interview data from one source with other sources. Results: This study reveals that the sustainability of agriculture in Gondangmanis Village requires effective management and policy support from the government. Farmers, the government, and the community must collaborate to improve agricultural productivity and minimize the risk of land conversion. Additionally, utilizing the latest technology is essential to ensure sustainable food security in Gondangmanis Village in the future. Applications/Originality/Value This study recommends that agricultural sustainability in Gondangmanis Village requires effective management and policy support from the government. This research aims to increase agricultural productivity in rural areas by promoting sustainable agriculture, which will provide long-term benefits and improve welfare for both the surrounding community and the environment.